Fullmetal alchemist. 17 - Arakawa, Hiromu, 1973- (VIZ Media, 2008)
A homunculus manages to breach impenetrable Fort Briggs, and the Elric brothers discover a terrible alchemical secret that pervades every corner of the world as they know it. Meanwhile, Major Kimblee and a ruthless General Raven make Major General Olivier Mira Armstrong an offer she can't refuse. Whose side is she on, really? And how far is she willing to go?"